Literasi Digital untuk Pencegahan Bullying dan Pembentukan Karakter Siswa - Siti Sufaidah; Muhammad Iqbal Nashrullah; Ibrahim Ibrahim; Arif Abdur Roofiq; Septian Dwi Wahyu; Mursyid Hero Sejati; M. Achsanul Khuluq Izzulchaq; Ahmad Nur Wahid; Chairul Anam (LPPM Universitas KH. A. Wahab Hasbullah, 2025)
The development of information and communication technology has led to the increasing use of social media among elementary school students. This condition poses serious challenges, particularly regarding low levels of digital literacy and the prevalence of bullying behavior, both directly and through social media (cyberbullying). This community service program aims to improve students’ digital literacy, especially in understanding morals and ethics in using social media. The program was carried out in three stages, namely preparation, implementation, and evaluation, targeting fourth to sixth-grade students. The partner in this activity was SDN Talun Kidul, involving the principal and teachers. The results of the program indicate positive changes among students. After the activity, students were able to distinguish between good and bad behavior, reduce the use of negative language, demonstrate mutual respect, and show the courage to reprimand peers engaged in bullying. The program concluded with an anti-bullying declaration as a collective commitment to creating a safe and conducive school environment. Thus, digital literacy socialization has proven effective in fostering students’ wisdom, empathy, and social responsibility. This program is recommended to be implemented sustainably by involving students, teachers, parents, and schools to build a positive culture in the use of social media.